A study of relationship between body mass index and short term outcome of isolated coronary artery bypass graft surgery - Azhar, AH; Zulkarnain, H; Ziyadi, G; Rahman, MNG (Department of Surgery, UKM Medical Centre, 2011)
Coronary artery disease (CAD) is the most common cause of death in the industrialized world. Obesity is one of the risk factor for developing CAD and also postoperative morbidity and mortality. However, in published articles the relationship between body mass index (BMI) and outcome of coronary artery bypass graft surgery depict conflicting results. This study evaluated the relationship between BMI and outcome of isolated coronary artery bypass graft performed in Hospital Universiti Sains Malaysia (HUSM). Cardiothoracic Unit HUSM is a referral centre for east coast of West Malaysia. Data was retrospectively collected from the medical records retrieved from the hospital record office. All patients who underwent isolated CABG in Cardiothoracic Unit, Hospital Universiti Sains Malaysia Kubang Kerian, Kelantan from November 2001 till October 2004 were identified and their demographic and clinical data were collected. Patients were divided into non overweight (BMI= or <25 kg/m2) and overweight (BMI>25 kg/m2) group. Data was then analyzed using SPSS version 12.0. There were 141 patients who underwent isolated CABG over the three year period. There were 80 patients with BMI < or =25 kg/m2 and 61 patients with BMI of >25 kg/m2. The demographic data of the two groups were similar. There was no statistical significant differences in the outcome of isolated coronary artery bypass graft. In conclusion, body mass index does not influence the outcome of isolated coronary artery bypass graft.